SUKUK PADA PERBANKAN SYARIAH: Analisis Dampak Ekonomi - Maldi Syahputra (Fakultas Studi Islam Universitas Muhammadiyah Riau, 2025)
Indonesia has great potential in developing sharia financebecause the majority of the population is Muslim and has degreeshigh economic growth. One of the main instruments infinancing is the issuance of State Sharia Securities (sukuk), whichfurther strengthening the government's ability to manage the deficitbudget. The government also has various options for determining the combinationthe most suitable financing instrument. This research aims toexamine: 1) the development and role of sukuk in Indonesia; 2) the impact of sukukon the Indonesian economy. The method used is approachqualitative with library research techniques, where the datasecondary are taken from various literature and references. Research resultshows that: 1) Issuance of State Sukuk continues to increase from year to yearto year, in line with the strategy implemented in the APBN; 2) Government Sukukprovide a significant positive impact, such as supporting financingdevelopment projects, encouraging the growth of the Islamic financial market,creating new business opportunities in the sharia financial sector, providingalternative investment instruments, and optimizing the use of fundspublic.